2013
DOI: 10.1111/dote.12154
|View full text |Cite
|
Sign up to set email alerts
|

Concordance of studies for nodal staging is prognostic for worse survival in esophageal cancer

Abstract: Pretreatment clinical staging in esophageal cancer influences prognosis and treatment strategy. Current staging strategies utilize multiple imaging modalities, and often the results are contradictory. No studies have examined the implications of concordance of computed tomography (CT), positron emission tomography (PET), and endoscopic ultrasound (EUS) when used for the evaluation of nodal disease. The objective of this study was to determine if concordance of CT, PET, or EUS for nodal disease predicts worse o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 18 publications
2
2
0
Order By: Relevance
“…The present univariate and multivariate analysis indicated that tumor location (upper versus middle and lower thoracic) was associated with survival rate and may be an independent prognostic factor in esophageal cancer. In addition, the present study identified that lymph node involvement may be an independent prognostic factor for esophageal cancer, which was consistent with the results of previous studies (28,29). …”
Section: Discussionsupporting
confidence: 93%
“…The present univariate and multivariate analysis indicated that tumor location (upper versus middle and lower thoracic) was associated with survival rate and may be an independent prognostic factor in esophageal cancer. In addition, the present study identified that lymph node involvement may be an independent prognostic factor for esophageal cancer, which was consistent with the results of previous studies (28,29). …”
Section: Discussionsupporting
confidence: 93%
“…These results are consistent with data from a cohort of oesophageal cancer patients who underwent oesophagectomy [12]. This study also described an intermediate-risk group comprising patients with discordant staging investigations, in which DC patients had better over survival than C+ve patients.…”
Section: Discussionsupporting
confidence: 89%
“…Important treatment decisions often hinge on the classification of nodal metastases on PET/CT and EUS examinations. In a previous study, Dhupar et al [12] reviewed 615 patients with oesophageal cancer from a single centre who underwent oesophagectomy for survival outcomes based on concordance of staging investigations for nodal disease. In summary, the study found that patients with discordance in nodal staging between imaging modalities had a better overall survival than patients with positively concordant nodal staging.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, these patients were clustered early in the study period when diagnostic modalities, such as EUS and PET/CT, were less frequently applied, resulting in a high proportion of clinically understaged patients in this subgroup. Nonetheless, even with the most modern and thorough use of clinical staging modalities, discrepancies with pathologic stage continue to occur in as many as 20% of patients [10].…”
Section: Commentmentioning
confidence: 99%